"Soft" prevention: judicial administration and judicial control in the light of articles 34 and 34 bis of the antimafia code (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The article focuses on “soft prevention”, a tool aimed at neutralizing criminal conditioning on healthy companies, in the search for a balance between the free exercise of business activities and effective prevention of mafia infiltration into legal economics.The author describes the importance of the logic of non-confiscatory intervention on companies affected by occasional criminal conditioning. This legislative technique is aimed at anticipating repressive intervention. The text also highlights regulatory gaps which, in the absence of a systematic intervention on the matter, risk nullifying the strength of these prevention and control institutes, which are endowed with great potential and innovation.
Keywords: soft prevention; judicial control; mafia infiltration; business activities; occasional facilitation